Length-Weight Relationship of Two Snow Trout, Schizothorax Richardsonii (Gray, 1832) and Schizothorax Plagiostomus (Heckel, 1838) from Kameng Drainage, Eastern Himalaya, India - K. Kunal; P. A. Ganie; Garima; D. Baruah; S. P. Shukla; A. K. Jaiswar; D. Sarma (Journal of Indian Fisheries Association, 2021)
Length- weight relationship (LWR) was studied for two Schizothorax species of snow trout collected from Kameng drainage for the period of two years (2018-19). LWR of these snow trout species from the Kameng drainage is not reported. The relationship was determined for male, female and for combined sexes of both the species. The relationship was established for S. richardsonii (Gray, 1832) as W=0.01502L2.773 (male), W=0.01163L2.773 (female) and W=0.01233L2.855 (combined), while for S. plagiostomus (Heckel, 1838) W= 0.01895L2.688 (male), W=0.03438L 2.501 (female) and W=0.02187 L2.645 (combined). In all the three categories the value of b was less than 3 for both the species which show negative allometric growth pattern. The value of K was below one which revealed that both the selected species possess lean body. Thus the value Kn obtained was greater than 1 that indicated the good condition of the fishes.